2016
DOI: 10.1007/s00432-016-2133-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of EGFR tyrosine kinase inhibitors for non-adenocarcinoma lung cancer patients harboring EGFR-sensitizing mutations in China

Abstract: EGFR TKIs could be an option for the treatment of EGFR-mutated non-adenocarcinoma NSCLC, especially for patients with adenosquamous histology and non-smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
2
21
1
Order By: Relevance
“…Patients with adenocarcinoma had a higher mutation rate than those with non-adenocarcinoma (50.2% vs 17.0%, P <0.001). A retrospective analysis in 2016 tested 597 non-adenocarcinoma NSCLC patients,9 and the EGFR mutation rate was 12.9%. Cho et al reported 1,255 patients with advanced NSCLC who accepted gefitinib at Samsung Medical Center between January 2007 and July 2010 10.…”
Section: Efficacy Evaluation Of Tkis In Egfr-mutated Non-adenocarcinomasmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with adenocarcinoma had a higher mutation rate than those with non-adenocarcinoma (50.2% vs 17.0%, P <0.001). A retrospective analysis in 2016 tested 597 non-adenocarcinoma NSCLC patients,9 and the EGFR mutation rate was 12.9%. Cho et al reported 1,255 patients with advanced NSCLC who accepted gefitinib at Samsung Medical Center between January 2007 and July 2010 10.…”
Section: Efficacy Evaluation Of Tkis In Egfr-mutated Non-adenocarcinomasmentioning
confidence: 99%
“…The efficacy of TKIs in EGFR-mutated squamous carcinoma was not very good, the response rate was 26.7%–38.0%, and the mPFS was 3.1–3.98 months (Table 3). Xu et al tested EGFR mutation in 597 non-adenocarcinoma NSCLC patients,9 and the squamous carcinomas among them were 457. The number of patients harboring EGFR mutation was 47, and 26 patients among them accepted TKIs (including gefitinib, erlotinib, and icotinib); the response rate was 30.8% and the mPFS was 3.98 months.…”
Section: Efficacy Evaluation Of Tkis In Egfr-mutated Squamous Carcinomasmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decade, the superior response of pulmonary adenocarcinoma with EGFR mutations to TKIs has changed the treatment guidelines, especially for elderly patients and those with locally advanced or metastatic pulmonary adenocarcinoma [6]. More recent research has also confirmed the presence of EGFR mutations in other types of lung cancer [7] and in triple negative breast cancer [4]. However, the EGFR mutation rate is extremely low in non-adenocarcinoma NSCLC.…”
Section: Discussionmentioning
confidence: 99%